Understanding the Triggers of English-Speaking Anxiety among University Students: A Cross-Cultural Mixed-Methods Study - Tauqeer Ali Rajpar; Abdul Malik Abbasi; Abdullah Laghari (Scientia Publica Media, 2026)
This study investigates the prevalence and underlying triggers of speech anxiety among ESL undergraduate students at the institute in Pakistan. The study is primarily grounded on Krashen’s Affective Filter Hypothesis (1988), Horwitz et al.’s Foreign Language Anxiety framework (1986), and Brown’s (2000) socio-affective and personality constructs, using these theories to interpret English speech anxiety in ESL learners. Recognizing English as both an official language and a critical tool for academic and professional advancement, the research examines how the pressure to speak flawlessly can lead to heightened anxiety, self-consciousness, and performance impediments in the classroom. Employing a mixed-methods approach, the study first distributed a 30-item Likert-scale questionnaire to 40 BS English students to quantitatively gauge anxiety levels, followed by semi-structured interviews with a subset of 10 students and several English language teachers to explore the contextual and personal dimensions of communication apprehension. The findings reveal that many learners experience significant nervousness and fear-manifested through physical symptoms such as trembling and mental blocks-when required to speak publicly in English, which in turn undermines their fluency and self-esteem. The paper discusses effective strategies adopted by students, such as practicing with peers, extra tutoring, and reading aloud, and underscores the need for educators to foster supportive classroom environments that reduce performance pressure while encouraging active participation. These insights offer valuable implications for language instruction and curriculum design aimed at mitigating speech anxiety and enhancing overall language proficiency. ESL teaching should nurture supportive classrooms, lower evaluation anxiety, and boost student confidence. Curriculum and teacher training should focus on spoken interaction and minimizing stressors. The study recommends future research on the long-term impact of anxiety reduction on language fluency, broader sampling, cross-institutional or cross-cultural comparisons, and qualitative work to improve interventions for ESL learners.